Eco-Psychological and Phenomenological Approach to Sustainability - Riggs, Larry W.; Hellyer-Riggs, Sandra (European Journal of Sustainable Development, 2019)
Our purpose is to show the value of eco-psychology and phenomenology for a cognitive paradigm fostering sustainable development. Our hypothesis is that those fields help lay the groundwork for truly sustainable development. Our method is a review of scholarly and theoretical work on the origins of the modern paradigm that has governed conceptions of development, and on eco-psychology, phenomenology, cognitive science, and sustainable development. Our contribution is a fully informed understanding of psychological and socio-cultural issues relevant to sustainability. The prevailing conception of development derives from the origins of modern science in seventeenth-century Europe. Francis Bacon and René Descartes elaborated a vision of development, or material progress, based on exploitation of a nature without inherent value, as a source of raw materials for human purposes. Eco-psychology aims to repair the rift between humanity and nature. Our dominant idea of development implies the alienation from nature that makes it difficult to prioritize authentic sustainability. Maurice Merleau-Ponty makes the crucial point that “we can never grasp the world in its totality but we grasp it according to the mode in which we inhabit it” (Merleau-Ponty, 1962, as cited in Buckley, 2013). What will we sustain? How will we negotiate the socio-cultural and psychological obstacles and achieve reconciliation? What are some examples of meaningful, practical movement toward sustainability? Keywords: eco-psychology, phenomenological, sustainability, mindset/paradigm, mindfulness, emotions, healing